2016
DOI: 10.1007/s10863-016-9643-2
|View full text |Cite
|
Sign up to set email alerts
|

Short ischemia induces rat kidney mitochondria dysfunction

Abstract: Renal artery clamping itself induces renal ischemia which subsequently causes renal cell injury and can lead to renal failure. The duration of warm ischemia that would be safe for postoperative kidney function during partial nephrectomy remains under investigations. Mitochondria play an important role in pathophysiology of ischemia-reperfusion induced kidney injury, however relation between ischemia time and mitochondrial dysfunction are not fully elucidated. Thus, the effects of renal ischemia (20 min, 40 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The model of 20 and 40 min kidney ischemia in vitro was chosen because, according to our results [ 15 ], 20 min was the shortest period of ischemia that induced statistically significant changes in renal mitochondrial respiratory functions. Moreover, our results showed that 40 min of kidney ischemia induced much more severe mitochondria structural and metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The model of 20 and 40 min kidney ischemia in vitro was chosen because, according to our results [ 15 ], 20 min was the shortest period of ischemia that induced statistically significant changes in renal mitochondrial respiratory functions. Moreover, our results showed that 40 min of kidney ischemia induced much more severe mitochondria structural and metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural investigation revealed that CAPE had protected from ischemia (20 min)-induced mitochondrial damage. Previously, we have demonstrated that ischemia mainly affects the mitochondrial intermembrane space, where intracristal space was found enlarged resulting in ballooned cristae as well as enlarged peripheral space followed by detachment of outer and inner membranes [ 15 ]. Application of CAPE preserved intermembrane space from edema after 20 min of ischemia, as it was found narrow and uniform in all experimental groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ischemia-reperfusion injury. Kidney IRI is a frequent cause of AKI after major surgery and following kidney transplantation that is characterized by PGC-1α downregulation and mitochondrial dysfunction [31,[171][172][173][174][175][176]. Kidney PGC-1α is reduced within 24 hours of kidney IRI, and PGC-1α-deficient mice had more severe AKI and accumulated fatty acids in tubular cells.…”
Section: Pgc-1α In Akimentioning
confidence: 99%